Intangible and tangible investments and future earnings volatility - Taoufik Elkemali (Economies, 2024)
This study delves into the impact of intangible and tangible investments on future earnings volatility within the European financial market context. Drawing from International Accounting Standards (IAS) 16 and 38, we examine the intricate relationship between fixed assets, expenses, and the uncertainty surrounding forthcoming earnings. Our analysis reveals that intangible assets, often associated with heightened uncertainty and risk, contribute to increased earnings volatility compared to capital expenditures. Furthermore, we find that capitalizing intangible assets serves to alleviate uncertainty, resulting in lower earnings volatility compared to expensing them. Our exploration of industries' effects further reinforce these findings, with the effect of intangible and tangible investments on earnings volatility being more pronounced in high-tech industries than in low-tech industries. Additionally, our robustness test, utilizing goodwill as a proxy for intangible assets and property, plant, and equipment as a proxy for tangible assets, yields consistent results, further bolstering our findings.
Keywords: 330; advertising expenses; capital expenditures; earnings volatility; intangible assets; research and development expenses